2018
DOI: 10.12659/msm.910962
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 Promotes Osteosarcoma Cell Proliferation and Invasion via STAT3 Activation

Abstract: BackgroundInterleukin-22 (IL-22) is one of the cytokines secreted by T-helper 17 (Th17) cells. It belongs to the IL-10 cytokine family and influences a variety of immune reactions. Studies have indicated that IL-22 can promote cancer progression and metastases. However, the function of IL-22 in osteosarcoma (OS) remains unclear.Material/MethodsIn this study, the expression of IL-22 in the OS cell line was detected by qRT-PCR. The role of IL-22 in proliferation and invasion in OS cells was tested by MTT and Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…IL-22 has been reported to activate the STAT3 signaling pathway in cells and initiate downstream transduction signals (28)(29)(30), including in osteosarcoma cells (10). Therefore, the present investigated the effect of IL-22 expression on the STAT3 signaling pathway in DDP-treated osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…IL-22 has been reported to activate the STAT3 signaling pathway in cells and initiate downstream transduction signals (28)(29)(30), including in osteosarcoma cells (10). Therefore, the present investigated the effect of IL-22 expression on the STAT3 signaling pathway in DDP-treated osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence shows that elevated levels of IL-22 in several malignancies is detrimental (15-18). In the present study, the study (10). The ability of IL-22 to regulate the sensitivity of osteosarcoma cells to cisplatin and its molecular mechanism was also investigated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…IL-22 has been suggested to regulate the progression of several tumors [10][11][12] but its involvement in breast cancer metastasis is largely unknown. To determine the potential involvement of elevated IL-22R1 and S1PR1 expression in breast cancer metastasis to distant organs, we analyzed a cohort of 65 breast cancer patients harboring a metastasis at a non-mineral site (lung and liver), brain, or bone.…”
Section: The Elevated Co-expression Of Il-22r1 and S1pr1 Is Associatementioning
confidence: 99%
“…Interleukin-22 (IL-22) is a key effector cytokine that plays a role in the pathogenesis of several inflammatory diseases including cancer [9]. Several lines of evidence have suggested that IL-22 signaling may regulate tumor progression by promoting cell growth and survival [10][11][12]. In further support of this, the aberrant expression of the IL-22 cognate receptor, interleukin-22 receptor 1 (IL-22R1), has been observed in many types of tumor, including lymphomas [13] and pancreatic [14], lung [15], and colon cancers [16].…”
Section: Introductionmentioning
confidence: 99%